Environmental Management Influence for Shade Trees on the temperature Reduction of yhe building. - Khunthong, Thanawuth; ., . (International Journal of Engineering and Technology, 2018)
Thailand is located in a humidÂ tropical climate and nearÂ the equator. ThusÂ the average air temperature is high throughout theÂ year.Â Environmental factorsÂ Â factorsÂ Â suchÂ asÂ theÂ sun,Â windÂ andÂ humidity affectsÂ Â residential buildings especially, heatÂ fromÂ the sunÂ is a mainÂ factor,Â whichÂ leadsÂ a problems of heatÂ insideÂ theÂ buildings (Prawewan Amornpong, 2001).Â Therefore, Installling air conditioning insideÂ the buildings is the solution for thisÂ problem. However, fromÂ theÂ studyÂ onÂ theÂ properties ofÂ plantsÂ it wasÂ foundÂ thatÂ plantsÂ areÂ effective in blockingÂ theÂ Â sun'sÂ Â raysÂ Â asÂ wellÂ Â asÂ effectivelyÂ maintainingÂ theÂ Â airÂ Â temperatureÂ inÂ theÂ Â areaÂ Â (Soontorn Boonyathikarn, 1999).Â So, planting treesÂ to prevent the sunlight, as shadeÂ to reduceÂ sun heatÂ in the buildings shouldÂ Â beÂ anÂ approach, whichÂ Â couldÂ Â beÂ adopted toÂ decrease theÂ useÂ ofÂ airÂ conditioning andÂ alsoÂ energy consumption in buildings (Trungjai Buranasompob, 2000).Â ThisÂ research aimsÂ (1) to studyÂ andÂ createÂ design guidelines on landscape models whichÂ conforms to the environment of sunlight and windÂ in the central region of Thailand and (2) to propose the guidelines on architectural landscape designs and plantsâ€™Â settingÂ around the buildings in 8 directions; NorthÂ (N),Â Northeast (NE),Â EastÂ (E),Â Southeast (SE),Â SouthÂ (S),Â Southwe st (SW), WestÂ (W)Â and Northwest (NW).Â The resultsÂ Â foundÂ that the landscape modelÂ included the settingÂ on plantsÂ as shadeÂ at all sidesÂ of the building envelope duringÂ 08.00-17.00 PM Â of the dayÂ throughout the year.Â TheseÂ can reduceÂ theÂ airÂ temperature of theÂ building envelope as wellÂ as theÂ average temperature insideÂ theÂ buildings, this showed a decrease in temperature by as muchÂ as 3.95Â°C or 13.478% compared withÂ the average exterior air temperature of the buildings throughout the year.Â Â Â